The Spiritual Exercises as an Ecumenical Strategy. (June 2014) - Haight, Roger
The ecumenical movement, proceeding comparing doctrines and ecclesial structures that divide, has foundered. The article suggests turning to what all churches share in common as a new starting point, namely, an ecclesial spirituality of following Jesus. The Spiritual Exercises of Ignatius Loyola can help bring this bond of unity to the surface. Negotiating on the basis of this common possession will allow the ideal of a pluralistic unity to take hold and encourage ecclesial structures that protect and honor rather than exclude different church traditions.